1975
DOI: 10.1007/bf01070753
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ascites: Diagnostic importance of ascitic lipase

Abstract: 10 cases of pancreatic ascites are presented. Ascitic fluid lipase is complementary to the determination of ascitic amylase in the diagnosis of pancreatic ascites and may be a more reliable diagnostic indicator of pancreatic ascites on a random ascitic fluid sample. Conservative management, consisting of abdominal paracentesis with or without diurectics, proved to be the treatment of choice in 3 of our patients who failed to reveal an associated pseudocyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…72 Ascitic fluid lipase has also been suggested to be useful in the diagnosis of pancreatic ascites. 73 Tumour markers (is it malignant?) A number of different proteins have been evaluated for their utility in diagnosing malignancy-related ascites.…”
Section: Amylase (Is Pancreatitis the Cause?)mentioning
confidence: 99%
See 1 more Smart Citation
“…72 Ascitic fluid lipase has also been suggested to be useful in the diagnosis of pancreatic ascites. 73 Tumour markers (is it malignant?) A number of different proteins have been evaluated for their utility in diagnosing malignancy-related ascites.…”
Section: Amylase (Is Pancreatitis the Cause?)mentioning
confidence: 99%
“…72 Ascitic fluid lipase has also been suggested to be useful in the diagnosis of pancreatic ascites. 73…”
Section: Tests Used In the Biochemical Analysis Of Peritoneal Fluidsmentioning
confidence: 99%
“…suggestions raised gamma-glutamyltransferase activity does not have the same diagnostic value.8 A serosanguinous fluid with an amylase activity greater than 20 000 Somogyi units and raised lipase activity is said to be a reliable indicator of pancreatic ascites. 9 The serum activity of lactate dehydrogenase is lower than that in the ascitic fluid in malignant ascites and the ratio is reversed in cirrhosis; the accuracy of the test may be improved by also calculating the ratio of serum to ascitic total protein.10 Normally, sterile ascites contains fewer than 300 x 106 white blood cells/I (300/mm3) with under 25% polymorphonuclear leucocytes, and spontaneous bacterial peritonitis, occurring in about 10% of cirrhotics with ascites," should be suspected when the cell count exceeds 500 x 106/1 and over half the cells present are polymorphonuclear leucocytes. Culture and Gram and Ziehl-Nielsen staining should always be performed on a centrifuged sample.…”
Section: Diagnosis Of Ascitesmentioning
confidence: 99%
“…This typical configuration has been stated by numer ous authors (10,15,16,18,23,27,51). Lipase has been estimated in serum and ascites in 17 cases (2,7,15,31,49,56), the serum ascites ratio being similar as in the case of amylase. Wagner and Tolins (56) as well as Sileo et al (49), however, suggested from their cases that lipase might be more reliable in making the diagnosis o f pancreatic ascites.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…Lipase has been estimated in serum and ascites in 17 cases (2,7,15,31,49,56), the serum ascites ratio being similar as in the case of amylase. Wagner and Tolins (56) as well as Sileo et al (49), however, suggested from their cases that lipase might be more reliable in making the diagnosis o f pancreatic ascites. Reduction o f serum albumin seems to be due to an increased loss o f albumin into the peritoneal cavity rather than to malab sorption or liver disease (48).…”
Section: Laboratory Findingsmentioning
confidence: 99%